From Bureaucratic-Centralism Management to School Based Management: Managing Human Resources in the Management of Education Program - Asad Asad (Universitas Jambi, Indonesia, 2021)
Indonesia’s education system used to be a centralized and bureaucratic mode as introduced by the Dutch as the colonial power. However, after the fall of Suharto’s administration in May 1998, the Indonesian education policy has significantly transformed from centralization to decentralization - which is popularly known as school-based management (SBM). This change is because of the arrival of the Law No.22/1999 (later reviewed by the Law 32/2004) about “Local Government” (provinces and districts). The purposes of this paper are first to discuss the characteristics of school-based management and the practices of SBM and second, to explore the motives of Indonesian government to apply school-based management in education in the digital era. The orienting question for this study is: Are all school-levels actors and district level actors ready for dealing with the characteristics of school-based management and the practices of SBM? Recommendations for education policy reform in the digital era in Indonesia for good governance are discussed, particularly the motives to move from bureaucratic-centralism management to school-based management.